Efektifitas Pelayanan Di Perusahaan Pengadaan Barang/Jasa Studi Kasus Pada CNOOC SES. Ltd - Nur Arafat (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2013)
The purpose of this study is (1) assess the effectiveness of services in Counter Bidding Procurement Department (CNOOC SES. Ltd) seen from queuing theory, and (2) assess the perception of partner companies with the services provided by the Counter Bidding Procurement Department. Of the effectiveness of services is viewed from the queue, the Department of Procurement Services is still relatively good, both at work I and II working hours. In terms of perceptions of partner companies to the Department of Procurement Services, of the 30 respondents drawn stating that the need for improvement in the service system. It happened because the source queue that takes times and costs for both partner companies / vendors, as well as for his own company CNOOC.